2020
DOI: 10.1038/s41467-020-15262-4
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional gersiloxenes with tunable bandgap for photocatalytic H2 evolution and CO2 photoreduction to CO

Abstract: The discovery of graphene and graphene-like two-dimensional materials has brought fresh vitality to the field of photocatalysis. Bandgap engineering has always been an effective way to make semiconductors more suitable for specific applications such as photocatalysis and optoelectronics. Achieving control over the bandgap helps to improve the light absorption capacity of the semiconductor materials, thereby improving the photocatalytic performance. This work reports two-dimensional −H/−OH terminal-substituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 61 publications
(91 reference statements)
0
97
0
Order By: Relevance
“…An immense amount of materials has been applied to catalyze the sunlight‐driven CO 2 reduction or H 2 evolution, including transition‐metal compounds, carbonaceous materials, porphyrin‐contained MOFs, and so on . Among them, the transition‐metal compounds exhibit remarkable performance.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…An immense amount of materials has been applied to catalyze the sunlight‐driven CO 2 reduction or H 2 evolution, including transition‐metal compounds, carbonaceous materials, porphyrin‐contained MOFs, and so on . Among them, the transition‐metal compounds exhibit remarkable performance.…”
Section: Figurementioning
confidence: 99%
“…[10,11] An immense amount of materials has been applied to catalyze the sunlight-driven CO 2 reduction or H 2 evolution, including transition-metal compounds, carbonaceous materials, porphyrin-contained MOFs, and so on. [12][13][14][15][16][17][18] Among them, the transition-metal compounds exhibit remarkable performance. Notably, we found that cobalt compounds demonstrate promising performance towards photocatalysis for its abundance and high performance.…”
mentioning
confidence: 99%
“…Scientists are now moving to exploit these intriguing nanomaterials for real-life applications. For energy scavenging applications, 2D nanomaterials are being used in (i) solar energy scavenging such as photovoltaic cells [ 6 ], perovskites [ 7 ], photocatalysis [ 8 ]; (ii) mechanical energy scavenging such as triboelectric [ 9 ] and piezoelectric devices [ 10 ]; (iii) thermal energy scavenging such as thermoelectric [ 11 ] and pyroelectric systems [ 12 ]; and (iv) chemical energy scavenging such as osmotic power generation [ 13 ]. 2D nanomaterial-based nanogenerators are potentially an attractive option for large-scale power generation from sustainable sources such as wind power, ocean waves, and rolling wheels [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…What's more, the band structure engineering of the photocatalysts, i.e. narrowing the bandgap to increase the visible light harvesting, the more positive shift of valence band (VB) energy to promotes easy oxidation of H2O to O2 and more negative conduction band (CB) energy to facilitate the photoreduction ability, is another key indicator for evaluating photocatalysts 22,23 . In this work, a novel carboxy-functionalized PVP-CdS nanopopcorns with hexagonal wurtzite (WZ)-cubic zinc blende (ZB) homojunction (named as MP-CdS) were synthesized via gamma-ray radiation-induced reduction and subsequent alkaline treatment under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%